Novel bipolar fluorescent polymers bearing N+P–O− resonance structures for fluorescent–phosphorescent (F–P) hybrid white polymer light-emitting diodes (WPLEDs). Issue 44 (18th April 2016) - Zhao, Qing-Hua; Fan, Zhu-Xin; Wang, Pei-Pei; Chu, Zhi-Wei; Su, Shi-Jian
Abstract : Two novel bipolar fluorescent polymers, PPOPAF andPPOCzF, were developed as blue emitters and hosts for an orange-red phosphor to realize fluorescent–phosphorescent (F–P) hybrid white polymer light-emitting diodes (WPLEDs). Abstract : Two novel fluorescent polymersPPOPAF andPPOCzF, with N + P–O − resonance structures inserted into the fluorene- alt -carbazole based backbone, were developed as blue emitters and hosts for an orange-red phosphor to realize fluorescent–phosphorescent (F–P) hybrid white polymer light-emitting diodes (WPLEDs). The polymers exhibit proper HOMO/LUMO energy levels, good thermal stability and high triplet energy ( E T ) levels. Devices usingPPOPAF andPPOCzF as single emissive layers show deep-blue emission with CIE coordinates of (0.16, 0.10) and (0.17, 0.10), respectively. Moreover, in hybrid white devices, doping with various concentrations of iridium(iii ) bis(4-phenylthieno[3, 2- c ]pyridinato-N, C 2 ) acetylacetonate (PO-01 ) (0.1%, 0.2%, 0.5 wt%), thePPOCzF -based devices give a significant improvement than that ofPPOPAF . While the doping concentration is 0.1 wt%, a nearly standard white emission (CIE: 0.35, 0.33) was achieved. The maximum CE, PE, EQE ofPPOCzF -based devices is 4.4 cd A −1, 1.1 lm W −1, and 1.7%, respectively.